PENGARUH HARGA DAN PROMOSI TERHADAP TINGKAT PENGGUNA JASA PENGIRIMAN DI JNE CABANG SAMARINDA - Aisyah Rayyani (OBOR: Oikonomia Borneo, 2019)
This study aims to determine how much influence price and promotion have on the level of users of delivery services at JNE Samarinda branch. perceived by consumers who use JNE Samarinda branch. The model used in this research is a questionnaire and literature study using a Likert scale and the method of determining the sample used is the Slovin formula as many as 100 samples with a population of 24,090. The analytical method used is validity test, reliability test, multiple linear regression analysis, coefficient of determination test and hypothesis testing, namely partial significant test (T) and simultaneous significant test (F) with the help of SPSS version 22 computer program to determine the effect of each variable. . The results of the study stated that the independent variables namely price and promotion had a positive influence on the dependent variable of service users with a value of 57%. With these results, the proposed hypothesis is accepted